An integrative approach in the management of human-wildlife conflicts : the case of the French brown bear - Piédallu, Blaise (HAL CCSD, 2016)
The conservation of controversial animal populations requires an understanding of the species’ ecology, but also an analysis of the human attitudes towards its presence. However, those two aspects are rarely studied together through a combination of environmental sciences and sociology. Here we study the brown bear (Ursus arctos) population residing in the Pyrenees mountains, analyzing both population dynamics and distribution, and the attitudes of Pyrenean people towards the species. We also ponder on the methods to use to combine these results in a socio-ecological approach. Our ecological models, which use monitoring data obtained through a crossborder partnership between France, Andorra and Spain, highlight an increase of population size and a reduction of its distribution between 2008 and 2014. If those conclusions do not seem to indicate a quick degradation of their conservation status, Pyrenean brown bears remain threatened by low numbers and high inbreeding in the population. A sociological study was performed in the municipalities where bear was or had been present between 2008 and 2013. We found spatial heterogeneity in the attitudes of Pyrenean people regarding bears, with significant variations depending on where they were born and where they currently live. We follow by discussing an approach that combines sociological and ecological results, with the goal of building a model that can be used as a tool for someone responsible for managing or solving the conflict; to do this, we analyze the methods available, their strengths and limits. We conclude on the importance of interdisciplinary approaches when managing controversies over wildlife conservation. La conservation des populations animales autour desquelles existe une controverse passe entre autres par une compréhension de l’écologie de l’espèce, mais également par une analyse des attitudes humaines vis-à-vis de sa présence. Cependant, ces deux aspects sont rarement mobilisés ensemble au sein de travaux combinant sciences de l’environnement et ...